(NrASSKAZY(B, (NPOWESTI(B, (NPXESY (B/s - (NgORXKIJ(B, (NmAKSIMs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1987)
(Nw KNIGU WKL@^ENY RANNIE RASSKAZY m(B.(NgORXKOGO (B"(NmAKAR ~UDRA(B", "(NsTARUHA iZERGILX(B", "(N~ELKA[(B" (NI DRUGIE(B, (NA TAKVE PXESY (B"(NnA DNE(B", (NI POWESTX (B"(NgORODOK oKUROW(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs; (NsOWETSKAQ LITERATURAs